New policies on skin-to-skin contact warrant an oxytocin-based perspective on perinatal health care - Bergman, Nils J. (Frontiers in Psychology, 2024)
Background In 2023, the World Health Organization (WHO) published a Global Position Paper on Kangaroo Mother Care (KMC), which is applicable to all countries worldwide: from the moment of birth, every “small and sick” newborn should remain with mother in immediate and continuous skin-to-skin contact (SSC), receiving all required clinical care in that place. This was prompted by the startling results of a randomized controlled trial published in 2021: in which 1,609 infants receiving immediate SSC were compared with 1,602 controls that were separated from their mothers but otherwise received identical conventional state-of-the-art care. The intervention infants showed a 25% reduction in mortality after 28 days. New perspectives The new WHO guidelines are a significant change from earlier guidance and common clinical practice. The author presents that separating mothers and babies is assumed to be “normal” (a paradigm) but actually puts newborns at increased risk for morbidity and mortality. The author presents arguments and ethical perspectives for a new perspective on what is “normal,” keeping newborns with their mothers is the infant’s physiological expectation and critical requirement for healthy development. The author reviews the scientific rationale for changing the paradigm, based on synchronous interactions of oxytocin on both mother and infant. This follows a critique of the new policies that highlights the role of immediate SSC. Actionable recommendations This critique strengthens the case for implementing the WHO guidelines on KMC for small and sick babies. System changes will be necessary in both obstetric and neonatal settings to ensure seamless perinatal care. Based on the role of oxytocin, the author identifies that many current routine care practices may actually contribute to stress and increased vulnerability to the newborn. WHO has actionable recommendations about family involvement and presence in newborn intensive care units. Discussion The concepts of resilience and vulnerability have specific definitions well known in perinatal care: the key outcome of care should be resilience rather than merely the absence of vulnerability. Newborns in all settings and contexts need us to re-evaluate our paradigms and adopt and implement the new WHO guidelines on KMC in perinatal care.